BLOOD HEMATOLOGICAL AND BIOCHEMICAL PROFILE OF BALI PIGS FROM TRADITIONAL AND CONVENTIONAL FARM SUPPLEMENTED WITH COMMERCIALLY MEAL - Putri, Putu Vindhy Chempaka; Mahardika, I Gede; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2022)
Experimental studies have been carried out to determine the weight gain, blood hematological and biochemical profile of weaning bali pig from traditional and conventional farms which are then given the same treatment as commercial feed. Weighing pigs is carried out every two weeks for two months. Examination of blood samples was carried out three times, at the beginning, middle and end of the study. The hematology profile was examined with a hematology analyzer. Cholesterol, triglycerides, and protein total were examined by photometer. The results showed that the weight gain of weaning pigs from traditional and conventional farms for 8 weeks was 13.81 kg and 14.19 kg (P>0.05). Overall range of erythrocytes; hematocrit; and hemoglobin in this study were 7.47-8.59 x 10 6 /µL; 37.23-44.78 %; and 11.95-14.17 g/dL, respectively. The total leukocyte range is 19.12-28.18 x 10 3 /µL; neutrophils: 0.49-7.19 %; eosinophils: 0.24-2.0 %; basophils: 0.73-5.18 %; lymphocytes: 16.22-83.02 %; and monocytes 1.21-6.82 %. The cholesterol range is 65.85-90.00 mg/dL; triglycerides: 30,75-78,81 mg/dL; and protein total: 5.0-6.6 g/dL. There was no statistically significant difference (P>0.05) between the average erythrocytes, hematocrit, hemoglobin, leukocytes total, leukocytes differential, cholesterol and protein total of piglets originating from traditional farm compared to those from conventional farm. However, there were significant differences (P<0.05) in triglyceride levels.